CITIZENS' ACCESS TO JUSTICE IN EUROPEAN AND INTERNATIONAL HUMAN RIGHTS LAW - Florin STOICA (Challenges of the Knowledge Society)
Access to justice is a fundamental pillar of the rule of law, enabling individuals to protect their rights, obtain remedies against unlawful acts, hold public authorities accountable, and benefit from fair procedural guarantees. This complex concept encompasses civil, criminal, and administrative law, serving both as a legal process and an indispensable tool for the exercise of other fundamental rights. But how accessible is the justice system, in reality, for citizens? What challenges persist in ensuring efficient and inclusive judicial mechanisms? At the international level, the UN Human Rights Committee has significantly contributed to defining and developing the principles of access to justice, influencing the interpretation of norms by bodies established under international treaties. Additionally, legal instruments such as the Aarhus Convention of 1998, which guarantees access to information and public participation in environmental matters, and the Convention on the Rights of Persons with Disabilities of 2006, which aims to eliminate legal barriers for vulnerable groups, underscore the importance of this right in specific contexts. However, the question remains: are these regulations sufficient to ensure real and effective access to justice for all?